A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea - Gardzińska, Joanna; Patoleta, Barbara (Zootaxa, 2013)
Diolenius sarmiensis sp. nov. is recorded, described and illustrated from New Guinea.